Sarcoidosis: a rare cause of Kleine-Levine-Critchley Syndrome - Afshar, K.; Engelfried, K.; Sharma, O.P. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2008)
Hypothalamic sarcoidosis is a rare entity that can alter the hypothalamic-pituitary axis and induce various combinations of endocrine changes.We present a case of neurosarcoidosis with uncommon features of hypersomnolense and hyperphagia. Current strategies to increase awareness and prevention of the harmful effects of obesity require clinicians to be cognizant of potential disorders that produce these features The mechanism, differential diagnosis and therapeutic options of this organic etiology are reviewed.